2014
DOI: 10.1007/s10753-014-9833-1
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Carvacrol on Acute Lung Injury Induced by Lipopolysaccharide in Mice

Abstract: Carvacrol, the major component of Plectranthus amboinicus, has been known to exhibit anti-inflammatory activities. The aim of this study was to investigate the effects of carvacrol on lipopolysaccharide (LPS)-induced endotoxemia and acute lung injury (ALI) in mice. Mice were injected intraperitoneally (i.p.) with LPS and the mortality of mice for 7 days were observed twice a day. Meanwhile, the protective effect of carvacrol (20, 40 or 80 mg/kg) on LPS-induced endotoxemia were detected. Using an experimental m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 25 publications
0
32
0
2
Order By: Relevance
“…Notably, the inflammation-dampening properties of exogenous carvacrol was not restricted to the intestinal tract, but could also be observed in extra-intestinal organs such as liver, kidneys and lungs as indicated by less distinct apoptosis and secretion of the pro-inflammatory cytokines TNF and IFN-γ in respective organs. In support, carvacrol has been shown to improve survival during LPS-induced endotoxinemia and acute lung injury in mice and to result in less distinct secretion of pro-inflammatory cytokines including TNF and IL-6 [53].…”
Section: Discussionmentioning
confidence: 96%
“…Notably, the inflammation-dampening properties of exogenous carvacrol was not restricted to the intestinal tract, but could also be observed in extra-intestinal organs such as liver, kidneys and lungs as indicated by less distinct apoptosis and secretion of the pro-inflammatory cytokines TNF and IFN-γ in respective organs. In support, carvacrol has been shown to improve survival during LPS-induced endotoxinemia and acute lung injury in mice and to result in less distinct secretion of pro-inflammatory cytokines including TNF and IL-6 [53].…”
Section: Discussionmentioning
confidence: 96%
“…Mice were anesthetized with isoflurane (2%) (24), and LPS was intratracheally instilled (Serotype 026:B6/L3755; Sigma‐Aldrich, St. Louis, MO, USA). Each animal received 50 μl of an LPS solution (5 mg/kg) (16). The control group received an intratracheal instillation of the same volume of saline.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has showed that treatment with rutin possesses the cardioprotective function of antioxidant effect and alteration of TNF-α level in diabetic rats (Saklani et al, 2016). In LPS-induced sepsis, treatment with rutin can improve acute lung injury via inhibition of oxidative stress and inflammatory response, which is characterized by increasing the activity of SOD and CAT, and inhibiting the level of TNF-α and IL-1β (Yeh et al, 2014;Chen et al, 2014;Feng et al, 2014). Thus, we assumed that rutin had a cardioprotective function against sepsis because of its antioxidant and anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%